Revisiting the ‘Siliconisation of Asia’: industrial policies and creative cluster in Malaysia - Abd Manan, Mohd Shahrudin (Universiti Putra Malaysia, 2019)
This paper explores the relationship between industrial policies and creative cluster in Malaysia. While most developed countries have leveraged the benefits of creativity and innovation for high-income economy, developing countries, like Malaysia, otherwise have been struggling to replicate the same success. Responding to this polemic, the article first frames the discussion on industrial policies and creative cluster with a reference to the spatial concept called, ‘the geography of innovation’. It is later followed with a specific historical review on the industrial policies and creative cluster in Malaysia since her independence in 1957. The review then becomes a basis for further reflecting the development of Cyberjaya city, a newly city aimed to be the national model of creative cluster. The article calls for more specific and contextualized researches on the issues of spatiality between the industrial policies and creative cluster, particularly in Malaysia as well as in the regional level of Southeast Asia that can benefit policy practitioners, economists, urban planners, academics and researchers alike.